IBI362 (LY3305677), a weekly-dose GLP-1 and glucagon receptor dual agonist, in Chinese adults with overweight or obesity: A randomised, placebo-controlled, multiple ascending dose phase 1b study. (September 2021) - Ji, Linong; Jiang, Hongwei; An, Pei; Deng, Huan; Liu, Meng; Li, Li; Feng, Liqi; Song, Baili; Han-Zhang, Han; Ma, Qingyang; Qian, Lei
Abstract: Background: IBI362 (LY3305677) is a novel weekly-dose glucagon-like peptide-1 and glucagon receptor dual agonist being developed for the treatment of obesity and type 2 diabetes. The aim of this randomised, placebo-controlled, multiple ascending dose phase 1b study was to evaluate the safety, tolerability, pharmacokinetics and efficacy of IBI362 in Chinese adults with overweight or obesity. Methods: This study enrolled adults with overweight (body mass index [BMI]≥24 kg/m 2 ) accompanied by hyperphagia and/or at least one comorbidity or obesity (BMI≥28 kg/m 2 ) from six study centres in China. Eligible participants were randomised 2:1 to receive once-weekly subcutaneous injection of IBI362 or placebo in each of the three ascending dose cohorts for 12 weeks with additional 8 weeks of safety follow-up. The dose-escalation regimens were: 3.0 mg cohort (1.0 mg weeks 1–4; 2.0 mg weeks 5–8; 3.0 mg weeks 9–12); 4.5 mg cohort (1.5 mg weeks 1–4; 3.0 mg weeks 5–8; 4.5 mg weeks 9–12); 6.0 mg cohort (2.0 mg weeks 1–4; 4.0 mg weeks 5–8; 6.0 mg weeks 9–12). The participants, investigators and study site personnel involved in treating and assessing participants within each cohort were masked to treatment allocation. The primary endpoints were safety and tolerability of IBI362. This study is registered with ClinicalTrials.gov, number NCT04440345. Findings: Between June 15 th, 2020 and January 15 th, 2021, 12 participants were enrolled and randomised in each cohort. Throughout the study, no participant discontinued the treatment due to safety reason and no serious adverse event was reported. Gastrointestinal adverse events and decreased appetite were the most common adverse events and mostly mild in severity. Three participants receiving IBI362 reported mild and asymptomatic cardiac disorders revealed by electrocardiogram. Estimated percent changes in mean body weight from baseline to week 12 were −4.81% (95%CI −6.61 to −3.02), −6.40% (−8.23 to −4.58) and −6.05% (−7.91 to −4.18) for participants receiving IBI362 in the 3.0 mg, 4.5 mg and 6.0 mg cohort, respectively, compared with 0.60% (−0.86 to 2.07) for those receiving placebo. Interpretation: IBI362 was well tolerated and showed a body weight-lowering effect in Chinese adults with overweight or obesity. Funding: Innovent Biologics.